Uso de medicamentos en el adulto mayor - Arriagada R., Leonardo; Jirón A., Marcela; Ruiz A., Inés (Revista Hospital Clínico Universidad de Chile, 2008)
The high growth of the elderly population has put health systems in situations never before seen. In parallel with the development of Geriatrics, in recent years, pharmacology has begun to investigate the changes in response to drugs related to human aging. Have been found changes in the pharmacokinetics and pharmacodynamics, which might explain because many drugs cause different responses in the elderly and because this age group has increased incidence and prevalence of adverse drug reactions. With the available data, it has been determined a group of potentially inappropriate medications in the elderly because the risks exceed the benefits. Inadequate use of drugs in the elderly patient leads to falls, delirium, hypotension, acute renal failure, abnormal electrolytic balance, among others, thereby generating more hospitalizations, adverse reactions, among others, which leads to increased dependency and deterioration of the functionality. For the previous reasons, the selection of drugs in the elderly patient mustconsider aspects pharmacokinetics, pharmacodinamics, cost - efficiency and safety profile from a perspective of the geriatrics, understanding that the drugs in these patients not always have the same response that an adult.